The Efforts of the National Library of Indonesia in Providing Covid-19 Reliable Resources through Coronapedia - Fanny Maharani; Ade Abdul Hak (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University of Jakarta., 2022)
The National Library of Indonesia has a very important role in creating reliable resources for the community during pandemic of Covid-19. The study is to understand the efforts of the National Library of Indonesia in increasing Covid-19 awareness through the development of “Coronapedia”. The method of this research is a case study approach. Data collection techniques were carried out using observation, in-depth interviews, literature review, and documentation. The results show the National Library has several efforts to improve Covid-19 understanding, especially during the pandemic. The National Library of Indonesia has developed a digital media-based environment, Coronapedia, as a feature of iPusnas that provides information resources in the pandemic era. In developing it, the National Library of Indonesia has several important things, including: 1) formulating the background of the importance of Coronapedia; 2) formulating goals to build Coronapedia; 3) building a Coronapedia collection; 4) building a network of information resources for the Coronapedia collection; 5) managing procurement and processing of Coronapedia collection. The many uses of Coronapedia as a trusted sources of Covid-19 information assisted people in sharpening their digital literacy about Covid-19. The significants of this research are expected to be able to make a positive contribution, as an evaluation material, to add insight, and to be used as a reference for further research on the effectiveness of the National Library of Indonesia in increasing Covid-19 information through the development of Coronapedia